ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MASYARAKAT DALAM MEMBUANG SAMPAH RUMAH TANGGA DI KOTA TIMIKA - Geldi Geldi; Inaran Mangiri; Muh Sabir (Jurnal Ekonomi dan Bisnis, 2023)
This research aims to determine the influence of environmental awareness, knowledge and availability of infrastructure on people's behavior in disposing of household waste in the city of Timika. To achieve this goal, the research method used is the associative method, the data collection techniques used are observation techniques and questionnaires using multiple linear regression analysis instruments. The results of the research show that environmental awareness and knowledge influence people's behavior in disposing of household waste in the city of Timika, while the level of infrastructure availability has no effect on people's behavior in disposing of household waste in the city of Timika.